Health education in adolescents: strategies and individual responses - Di Pietro, Maria Luisa (Medicina e Morale, 1997)
Over the last few years there has been an increase in so called "risktaking behaviour" among adolescents. This behaviour, is both directly and idirectly responsible for damaging the health and/or life of those involved and for increased incidence of morbidity and mortality in an age group that is least exposed to disease and death. The increased incidence of pathologies resulting from risk-taking behaviour has involved and is involving, in a precautionary sense, both the teaching staff and those responsible for public health who have proposed various models of intervention: fromm so-called "risk reduction" to the "fear strategy" to health education. This article aims to evaluate the effect of the various intervention strategies on adolescents' behaviour, in order to identify whether the failure or success depends on the contents of the prevention programme or on the personality of the students. This evaluation is preceded by an analysis of why adolescents have risk taking behaviour so often and in fact the knowledge of "why" is a fundamental element for establishing "how" (to intervene).